Flexural Behavior of Reinforced Concrete Beams Strengthened by Textile Reinforced Magnesium Potassium Phosphate Cement Mortar - Zhu, Cheng-Jie; Fang, Shuai; Ng, P. L.; Pundienė, Ina; Chen, Jia-Jian (Frontiers in Materials, 2020)
Magnesium potassium phosphate cement (MKPC), made of sintered magnesium oxide and potassium phosphate, is a new material for construction and structural repair. It possesses high early strength and bond capacity, low drying shrinkage, excellent fire resistance and compatibility with concrete. These characteristics render it an ideal material for strengthening reinforced concrete (RC) structures. This study developed a MKPC-based textile reinforced cementitious composite (TRCC) to strengthen RC beams at soffit. Three-point flexural tests were conducted on two control specimens without strengthening and two strengthened specimens. Experimental results showed that the TRCC system exhibits good bonding with substrate concrete. The strengthened specimens failed due to rupture of textile meshes in TRCC. TRCC could improve load capacity by 4%-25%, postpone propagation of cracks, reduce tensile strain of main reinforcement and reduce deflection of beams at the same load level. High relative textile ratios contributed to the load resistance while impaired the ductility of strengthened beams. Design formulae are proposed to predict the flexural capacity of beams strengthened by MKPC-based TRCC, and reasonable prediction close to experimental results can be obtained from the formulae.